Terminus Amnesia: Cherokee Freedmen, Citizenship, and Education. Issue 1 (2nd January 2016) - Chin, Jeremiah; Bustamante, Nicholas; Solyom, Jessica Ann; Brayboy, Bryan McKinley Jones
Abstract : In 2007, the Cherokee Nation of Oklahoma amended its constitution to limit membership to only those who can trace lineal descent to an individual listed as Cherokee by Blood on the final Dawes Rolls. This exercise of sovereignty paradoxically ties the Dawes Rolls, the colonial instruments used to divide the lands and peoples of the Cherokee Nation, and self-determination. In the process, it effectively disenrolls Cherokee Freedmen, the descendants of Blacks enslaved by the Cherokee Nation. In this article, we explore the implications of this history in the context of self-determination and sovereignty, particularly looking at the influence of colorism on the Dawes Rolls and its ongoing effects. Our goal is to share a piece of history that is often obscured or unknown; to explore how and to what extent the exercise of self-determination and sovereignty in Indigenous nations is impacted by colorism; and finally to consider implications for practice created by the disenfranchisement of peoples from Indigenous nations.